Profil darah ayam broiler fase finisher yang diberi ekstrak daun kelor (Moringa oleifera) dalam air minum: Blood profile of finisher phase broiler chickens given moringa leaf extract (Moringa oleifera) in drinking water - Sri Hartini; Martha Kayadoe; Dwi D. Rahardjo; Dwi Nurhayati (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2023)
Abstract The aim of the study was to determine the effect of Moringa oleifera (MO) leaf extract in drinking water on the blood profile of finisher broilers. A total of 140 broiler chickens at 21 days old were randomly allocated to 28 cages. Body weight per cage was 4433 ± 242.8 g (CV 5.48%). The experimental design was a completely randomized design with 4 (four) treatments and 7 replications. The four treatments were: P1 (1 L drinking water + 0 g MO leaves), P2 (1 L drinking water + 25 g MO leaves), P3 (1 L drinking water + 50 g MO leaves), and P4 (1 L drinking water + 75 g MO leaves). Moringa oleifera water was given with the patron of 3 days "on" and 2 days "off". Commercial feed was given ad libitum during the study. The variables measured were total erythrocytes, leukocytes, heterophils, eosinophils, lymphocytes, monocytes, Packed Cell Volume (PCV), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC). The results showed that the treatment had no significant effect (P>0.05) on all the variables measured. In conclusion, administration of Moringa oleifera leaf up to 75 grams in drinking water did not affect the blood profile of finisher broilers. Key word: Drinking water; Moringa oleifera; Blood profile; Erythrocytes total Abstrak Tujuan dari penelitian ini adalah untuk mengetahui pengaruh daripada pemberian ekstrak daun kelor (Moringa oleifera) dalam air minum terhadap profil darah ayam broiler fase finisher. Total 140 ekor ayam broiler umur 21 hari dialokasikan secara acak pada 28 unit kandang. Berat badan ayam per unit kandang adalah 4433 ± 242,8 g (CV 5,48%). Rancangan percobaan adalah Rancangan Acak Lengkap dengan 4 (empat) perlakuan dan 7 ulangan. Empat perlakuan yang diberikan yaitu: P1 (1 L air minum + 0 g daun kelor), P2 (1 L air minum + 25 g daun kelor), P3 (1 L air minum + 50 g daun kelor), dan P4 (1 L air minum + 75 g daun kelor). Air minum perlakuan diberikan dengan patron 3 hari “on” dan 2 hari “off”. Pakan komersial diberikan ad libitum selama penelitian. Variabel yang diukur adalah total eritrosit, leukosit, heterofil, eosinofil, limfosit, monosit, Packed Cell Volume (PCV), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), dan Mean Corpuscular Hemoglobin Concentration (MCHC). Hasil penelitian menunjukkan bahwa perlakuan tidak berpengaruh signifikan (P>0,05) terhadap semua variabel yang diukur. Kesimpulan, pemberian ekstrak daun kelor sampai dengan 75 gram dalam air minum tidak mempengaruhi profil darah ayam broiler fase finisher. Kata kunci: Air minum; Moringa oleifera; Profil darah; Total eritrosit